From the sea to aquafeed: A perspective overview - Eroldoğan, Orhan Tufan; Glencross, Brett; Novoveská, Lucie; Gaudêncio, Susana P.; Rinkevich, Buki; Varese, Giovanna Cristina; de Fátima Carvalho, Maria; Tasdemir, Deniz; Safarik, Ivo; Nielsen, Søren Laurentius; Rebours, Céline; Lada, Lukić Bilela; et al. (My University, 2022)
Aquaculture has been one of the fastest-growing food production systems sectors for over three decades. With its growth, the demand for alternative, cheaper and high-quality feed ingredients is also increasing. Innovation investments on providing new functional feed alternatives have yielded several viable alternative raw materials. Considering all the current feed ingredients, their circular adaption in the aquafeed manufacturing industry is clearly of the utmost importance to achieve sustainable aquaculture in the near future. The use of terrestrial plant materials and animal by-products predominantly used in aquafeed ingredients puts a heavily reliance on terrestrial agroecosystems, which also has its own sustainability concerns. Therefore, the aquafeed industry needs to progress with functional and sustainable alternative raw materials for feed that must be more resilient and consistent, considering a circular perspective. In this review, we assess the current trends in using various marine organisms, ranging from microorganisms (including fungi, thraustochytrids, microalgae and bacteria) to macroalgae and macroinvertebrates as viable biological feed resources. This review focuses on the trend of circular use of resources and the development of new value chains. In this, we present a perspective of promoting novel circular economy value chains that promote the re-use of biological resources as valuable feed ingredients. Thus, we highlight some potentially important marine-derived resources that deserve further investigations for improving or addressing circular aquaculture.
Keywords: Alternative protein; Aquafeed; Circular aquaculture; Fatty acid; Lipids; Single cell protein